Developing “ARMI” Medium to Encourage Students in Writing Simple Sentences of Simple Past Tense (RETAIN, 2018)
AbstractLearning to write simple sentences needs more than having the idea(s) and understanding language components. Writing skill is difficult for English foreign language learners because of lack of communication in English such as the society does not speak or write in English. Moreover when it comes to write in simple past tense, there are two factors which the students find it difficult, those are, the difficulties in the forms and in the usage. Thus, a suitable instructional media is made to overcome the students’ problems in writing simple past tense. This study aims to describe the development of an instructional media involving game called “ARMI Medium” to encourage students in writing simple sentences of simple past tense. It uses the modified cycle of R & D design adopted from Dick, Carey, and Carey (2015) to describe the development of this medium. The result shows that the medium successfully attracts the students’ interest in writing simple sentences in which the students in a group can produce good simple sentences in the end of this activity.Keywords: writing, media, game, ARMI medium, simple past tense AbstrakBelajar untuk menulis kalimat sederhana membutuhakan lebih dari memiliki ide-ide dan memahami komponen-komponen bahasa. Kemampuan menulis itu sulit untuk pelajar bahasa inggris sebagai bahasa asing dikarenakan kurangnya komunikasi dalam bahasa inggris, misalnya, masyarakat yang tidak berbicara atau menulis dalam bahasa inggris. Lebih-lebih jika itu berkaitan dengan menulis dalam simple past tense, ada dua faktor yang membuat siswa merasa kesulitan, yaitu kesulitan dalam bentuk dan kegunaannya. Oleh karena itu, media yang cocok dibuat untuk mengatasi masalah siswa dalam menulis simple past tense. Studi ini bertujuan untuk mendeskripsikan pengembangan sebuah media yang melibatkan permainan didalamnya bernama “media ARMI” untuk mendorong siswa dalam menulis kalimat simple past tense yang sederhana. Studi ini menggunakan desain R & D yang dimodifikasi dari Dick, Carey, and Carey (2015) untuk mendeskripsikan pengembangan media ini. Hasil penelitian ini menunjukkan bahwa media ini sukses menarik minat siswa dalam menulis kalimat sederhana yang mana siswa dalam kelompok bisa menghasilkan kalimat sederhana yang baik di akhir kegiatan.Kata Kunci: menulis, media, permainan, media ARMI, simple past tense